Oświata i nauka - Ośko, Stanisław (1929-2026) (1983)
Dotyczy regionu radomskiego.
Tytuł nagłówkowy.
Zawiera ilustracje.
Dostępny również w wersji elektronicznej.
Keywords: Edukacja -- Polska -- Radom (region) -- 1970-2000.